The Relationship Between Stress Levels and Quality of Life in Pulmonary Tuberculosis Patients - Dewi, Juli Krisna; Kusumaningtyas, Dwi Prima Hanis; Priastana, I Ketut Andika (Indonesian Journal of Global Health Research, 2024)
Tuberculosis (TB) infection is one of the diseases whose spread is influenced by environmental and behavioral factors. One of the psychological impacts felt by pulmonary TB patients is stress. Stress that the patient experiences over a long period of time and is not overcome will affect the patient's quality of life. The purpose of this study was to determine the relationship of quality of life of pulmonary tuberculosis patients who experience stress with the disease. The research design used in this study is correlation analytic. The population of this study was 62 and a sample of 54 respondents with a sampling technique that is consecutive sampling. Stress levels were measured using the Depression Anxiety Stress Scale (DASS 42) questionnaire. The quality of life of the respondents was measured by the St. George Respiratory Questionnaire (SGRQ) questionnaire. The research data was compiled using Microsoft Excel and then reviewed for completeness. The complete data was coded or underwent the coding process. Data on stress levels and quality of life for tuberculosis (TB) patients were categorical with a nominal scale, so the statistical test used was the Chi-Square Test. The results of analysis using Chi Square test obtained p-value of 0.000 or <0.05. The conclusion of this study is that there is a relationship between the level of stress with the quality of life of patients with pulmonary TB in the working area of the State Health Center II.